(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
The POCSO Act of 2012 stands as a pivotal legal instrument in India’s efforts to combat child sexual abuse. This review article critically examines the Act, with a specific focus on the amendments made since its inception. The analysis delves into the important points of the Act, the effects of recent amendments, enforcement strategies, challenges encountered, and the potential future direction of child protection within this legal framework.